Evaluation of Micro and Macro-level Coherence of Students Argumentative Essays in ESAWEEK Writing Competition - Shofyatul Fuadiyah; Sri Wuli Fitriati; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2022)
One of the most important aspects of writing a meaningful text is to achieve its coherence within the text. This study evaluated students' argumentative essays' micro and macro-level coherence in the ESA WEEK writing competition. This research is a qualitative study in the form of a discourse analysis approach by using the theory through the lens of micro and macro-level coherence (Thornburry, 2005). This study reveals several findings. Almost all the texts are sufficient to have good logical relations. The most frequent connections are additive and causal ties. In terms of logical relationships, the most frequent pattern in the texts was the zig-zag pattern, and the rarely used was the multiple rheme pattern. Even though all patterns were in texts, some rogue sentences were still found in each text. The keywords could represent the texts' topic or theme in almost every paragraph. It made readers guess the main issue quickly. Some writers could build a schema well, but others could not. Most of the texts organized in argumentative essays structure has Introduction-Body-Conclusion. This study can be used as a consideration to write meaningful and coherent text and references in the same field of discourse analysis.